2005
DOI: 10.1590/s1517-83822005000400007
|View full text |Cite
|
Sign up to set email alerts
|

Stpahylococcus aureus biofilms on central venous haemodialysis catheters

Abstract: Biofilm bacterial infections are common in patients undergoing treatment with haemodialysis. This study involved 16 patients (7 males, 9 females; ages from 22 to 81 with an average age of 50) who had had a total of 25 temporary haemodialysis polyurethane catheter insertions into the subclavian vein (22 dual-lumen and 3 triple-lumen). The catheters remained in place from 3 to 91 days, on an average of 47 days. The reasons for catheter removal were: bad functioning (44%), suspicion of catheter-related infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
2
4
0
2
Order By: Relevance
“…In accordance with our findings, medical instruments were suggested as a common source of biofilm producing staphylococci (27,28). However, such high rates of biofilm producing isolates from wound and blood samples in our study are not uncommon, since several authors have shown high rates of biofilm formation among staphylococci obtained from these settings (29)(30)(31)). …”
Section: Discussionsupporting
confidence: 90%
“…In accordance with our findings, medical instruments were suggested as a common source of biofilm producing staphylococci (27,28). However, such high rates of biofilm producing isolates from wound and blood samples in our study are not uncommon, since several authors have shown high rates of biofilm formation among staphylococci obtained from these settings (29)(30)(31)). …”
Section: Discussionsupporting
confidence: 90%
“…20,21 Small sample size could be an analytical problem; however, our sample size is similar to other studies. 18,19,22,23 Only multicenter or large retrospective studies have larger samples. [24][25][26] We observed that the site of implant may be related to a greater or lesser predisposition to infection.…”
Section: Discussionmentioning
confidence: 99%
“…Nos cateteres semi-implantáveis de longa permanên-cia utilizados em hemodiálise, a infecção é a complicação tardia mais frequente 4 , sendo o Staphylococcus aureus o agente mais isolado 4,5 , seguido por bacilos gram-negativos e pelo Staphylococcus coagulase negativo 6 .…”
Section: Epidemiologiaunclassified